HUBUNGAN PERAN KADER DENGAN FREKUENSI KUNJUNGAN LANSIA DI PUSKESMAS KARANG MEKAR BANJARMASIN - Dewi Iswandari, Novita; Elvine Ivana Kabuhung (LPPM Universitas Sari Mulia, 2022)
Background: An important factor in the success of elderly posyandu (integrated health service posts) is family support and the role of health cadres. Family support can encourage the interest and motivation of the elderly to regularly visit the posyandu by facilitating or accompanying them to the posyandu, reminding them of the schedule, and helping overcome barriers to participation. The role of health cadres is also crucial, as they are the main drivers in achieving the goals of the elderly posyandu program. Objective: To determine the relationship between the role of health cadres and the frequency of elderly visits to the posyandu in the working area of Karang Mekar Health Center, Banjarmasin. Method: This was an analytical study using a cross-sectional approach. The population included all elderly individuals in the Karang Mekar Health Center working area. A total sampling technique was used, involving 47 respondents. Data were analyzed using the Chi-Square test. Results: The study found that the highest number of respondents perceived the role of cadres as good (28 people or 59.6%), while the highest frequency of elderly visits to the posyandu was categorized as inactive (30 people or 63.8%). Conclusion: There is no significant relationship between the role of health cadres and the frequency of elderly visits to the posyandu in the working area of Karang Mekar Health Center, Banjarmasin. Keywords: Role of Health Cadres, Visit Frequency, Elderly